New records, detailed distribution and abundance of rove-beetles (Insecta, Coleoptera, Staphylinidae) collected between 1990 and 2015 in Azores (Portugal) with an updated checklist - Borges, Paulo A. V. (2022)
Background: The dataset we present consists of an inventory compiling all records and knowledge about Staphylinidae (Insecta, Coleoptera) in the Azores and is part of a long-term monitoring performed between 1990 and 2015 in different habitat types of eight islands of the Azores Archipelago. Most samples come from the BALA project (Biodiversity of Arthropods from the Laurisilva of Azores) that sampled native forests in the Azores. Additional sampled habitats include exotic forests, intensive and semi-natural pasturelands, orchards, caves and lava flows. Most of the records (about 96.7%) were collected in standardised sampling campaigns, which included pitfall traps and beating transect protocols. Non-standardised records are based on hand-collecting and sifting, as well as cave, colour and malaise traps. New information: We provide a long-term inventory of Staphylinidae (Insecta, Coleoptera) collected in the course of several standardised sampling campaigns and recorded with non-standardised methods. We collected a total of 10744 specimens belonging to 69 identified species of Staphylinidae, which represents 51% of the species known from the Azores Archipelago. Four endemic species were sampled, representing 40% of the known Azorean endemic species. From this dataset, seven species are new for the Azores: Aleochara funebris Wollaston, 1864; Amischa forcipata Mulsant & Rey, 1873; Bledius unicornis (Germar, 1825); Carpelimus troglodytes (Erichson, 1840); Cypha seminulum (Erichson, 1839); Paraphloeostiba gayndahensis (MacLeay, 1871); Tachyporus caucasicus Kolenati, 1846. We also registered a total of 66 new island records for eight Azorean islands. This contribution continues a series of publications on the distribution and abundance of Azorean arthropods. We also provide an updated list of Azorean rove-beetles (Staphylinidae) that now includes 136 species, ten of them considered Azorean endemics.